The impression of influence : legislator communication, representation, and democratic accountability - Grimmer, Justin (Princeton University Press, 2015)
Constituents often fail to hold their representatives accountable for federal spending decisions-even though those very choices have a pervasive influence on American life. Why does this happen? Breaking new ground in the study of representation, The Impression of Influence demonstrates how legislators skillfully inform constituents with strategic communication and how this facilitates or undermines accountability. Using a massive collection of Congressional texts and innovative experiments and methods, the book shows how legislators create an impression of influence through credit claiming messages.